Computers! - Trainor, Timothy N. (Unites States of America : Mitchell Publishing, Inc., 1989)
This book is written in an easy-to-read style, supported by a variety of instructional photographs and drawings. A comprehensive instructor's manual and student study guide clearly identify chapter objectives and important concepts.
Unit I. Overview -- Unit II. Computer technology -- Unit III. Software: Concepts and applications -- Unit IV. Information systems -- Unit V. Looking ahead.
Includes bibliographical references and index.
Keywords: COMPUTERS